From Pig in a Parlor to Boar in a Boardroom: Why Ellerth Isn’t Working and How Other Ideological Models Can Help Reconceptualize the Law of Sexual Harassment - Bauchner, Kerri Lynn (Columbia Journal of Gender and Law, 1999)
Imagine that Beth works for corporation x, which has implemented proactive policies to prevent and deal with sexual harassment. Her supervisor, however, constantly makes inappropriate advances towards her, often threatening that her failure to comply with his requests will result in “complications” for her at the corporation. She finally tells him that she will not be intimidated and that she will report his behavior if it continues. The next week, she is excluded from a career-advancing conference that most others at her level of employment are invited to. She is also pulled from a big project she is working on, and loses the commission that she stood to make from her participation in the project. Now imagine that another woman, Bonnie, works for the same corporation x. Her supervisor also makes inappropriate advances and comments, making her feel objectified and degraded. He makes ambiguous statements, implying that certain people at the corporation will have a far easier time getting ahead than others, but he never actually threatens her. She is made to feel extremely uncomfortable. When she asks him to stop his behavior, he laughs and says he doesn’t know what she is talking about. Not long after, she receives her expected promotion along with the rest of her class, but continues to work for the same supervisor. Because Bonnie is too intimidated to report his tacit threats, and in light of her success at the corporation she fears ruining her chances of further advancement, she remains silent.